Relationship economics : transform your most valuable business contacts into personal and professional success - Nour, David (Hoboken : Wiley, 2011)
"Relationship Economics teaches the reader that success comes from learning how to invest in people and how to turn your most valuable relationships into results. Understanding and developing the three types of relationships- personal, functional, and strategic- will ultimately help you hone critical skills to not only develop a nose for identifying great opportunities, but which relationships to tap for execution, performance and results. The new paperback of the book will be revised and updated to include the following updates, among others: 1) new case studies and examples; 2) an updated resource recommendation list; and 3) a finalized set of relationship self- assessments for the reader to take"--
Includes index.
Keywords: Social networks -- Economic aspects